Dimensional Analysis of Retail Shop Images on Consumer Purchase Intention - Iswati, Heni; Yuwono, Yuwono; Meidiyustiani*, Rinny (JURISMA : Jurnal Riset Bisnis & Manajemen, 2023)
The research aims to determine the effect of retail store image on consumer purchase intention on private label brands. The method used is descriptive verification with a quantitative approach obtained by 217 respondents as a sample. The results of the study show that the regression calculation partially obtains products/merchandise, store atmosphere and customer service and has a significant and significant effect on consumer purchase intentions, but not on price because Private Label Brand (MPL) products do not affect consumer perceptions of buying. Consumers do not mind the price range that has been set by MPL, MPL products are of good quality at a lower price compared to national brands that have the same function. Keywords: Image Dimensions; Consumer Purchase Intention; Retail; MPL; Product